2019
DOI: 10.1109/access.2019.2921243
|View full text |Cite
|
Sign up to set email alerts
|

Cache-Assisted Broadcast-Relay Wireless Networks: A Delivery-Time Cache-Memory Tradeoff

Abstract: An emerging trend of next generation communication systems is to provide network edges with additional capabilities such as storage resources in the form of caches to reduce file delivery latency.To investigate this aspect, we study the fundamental limits of a cache-aided broadcast-relay wireless network consisting of one central base station, M cache-equipped transceivers and K receivers from a latency-centric perspective. We use the normalized delivery time (NDT) to capture the per-bit latency for the worst-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Examples of caching scheme under edge-only transmission for the achievable NDT in Proposition 1. The dashed lines identify the clusters of cooperative ENs in(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of caching scheme under edge-only transmission for the achievable NDT in Proposition 1. The dashed lines identify the clusters of cooperative ENs in(18).…”
mentioning
confidence: 99%
“…are sent to all m ENs in cluster K T i as in(18). Hence, each EN receives K R F (m − µK T )/K T packets on the fronthaul, yielding the fronthaul NDT δ F (m) = |F i |/F r = K R (m − µK T )/(K T r).…”
mentioning
confidence: 99%
“…Motivated by the extreme popularity of video streaming applications, the seminal work (Shanmugam et al, 2013) has shown that small cell dense networks can improve the spectral efficiency of the wireless system. The work (Kakar et al, 2019) studies a cacheenabled broadcast-relay wireless network from a latency-centric perspective. Furthermore, the authors in (Shanmugam et al, 2013) proposed to equip the BSs with local memory to cache the most popular content in order to alleviate the bottleneck of fronthaul/backhaul communications and efficiently provide the video content to users.…”
Section: Related Workmentioning
confidence: 99%
“…Motivated by the extreme popularity of video streaming applications, the seminal work [25] has shown that small cell dense networks can improve the spectral efficiency of the wireless system. The work [26] studies a cache-enabled broadcast-relay wireless network from a latency-centric perspective. Furthermore, the authors in [25] proposed to equip the BSs with local memory to cache the most popular content in order to alleviate the bottleneck of fronthaul/backhaul communications and efficiently provide the video content to users.…”
Section: B Related Workmentioning
confidence: 99%